The Effect of Carbonated Drinks on Blood Glucose Levels in Mice (Mus musculus) - Ruqiah Ganda Putri Panjaitan; Dahlia Dahlia; Eko Sri Wahyuni (Universitas Wiralodra, 2023)
The habit of people who live in cities and villages likes instant smells, for example, consuming soft drinks. One of the soft drinks popular in the community is carbonated drinks. This study aims to determine the effect of carbonated drinks on blood glucose levels of mice. This study used 21 male mice Balb C strain aged 2-3 months, which was divided into 3 groups, namely K1 given aquadest dose of 0.86 ml / 20 g body weight. K2 is given a carbonated drink dose of 0.43 ml / 20 g body weight. K3 was given a carbonated drink dose of 0.86 ml / 20 g body weight. All treatments were given for 14 days. The average increase in blood glucose levels of mice in KI, K2, and K3 were 16.71 mg / dl, 11.63 mg / dl, and 67.59, respectively (P<0.05). The results of the study showed that there was an increase in blood glucose levels in all treatments. However, the highest increase in blood glucose levels is in K3 (67.59 mg / dl). From the results of the study, it was concluded that carbonated drinks can affect blood glucose levels in mice, but this increase is still within normal limits.